They're giving you a big hint when they tell you that 52x - 13y = 13 × (4x - y)! If we look at the expression 28x - 7y, we might notice that both 28x and 7y have the factor 7 in common (since 28 = 7 x 4 and 7 = 7 x 1). With that in mind, we can factor that 7 out to rewrite it as
28x - 7y = 7 × (4x - y).
From here on out, I'm going to just take 4x - y and put it away inside another variable I'll call z. We can now rewrite both of our expressions much more simply:
13 × (4x - y) → 13z
7 × (4x - y) → 7z
The question also tells us that what we're now calling 13z is equal to 65. In equation form, this is
13z = 65
Dividing both sides by 13, we find that
z = 65/13 = 5,
and if z = 5, we can say that 7z = 7 × 5 = 35, which is exactly what we were looking for.